Prison provisions in Islam - العبودي م.م علي محمد ثامر (Thi Qar Arts Journal, 2021)
Praise be to God, Lord of the Worlds, and prayers and peace be upon the Master of the Messengers and the Seal of the Prophet Abi Al-Qassim Muhammad, the good and pure people of his household, and his close companions who walked on his gift and were his shadow, and upon those who followed them until the Day of Judgment and after ... Imprisonment and imprisonment have known humanity in its long history, and the prisoner used to receive the most severe forms of torment before Islam and had no rights ... And when Islam came as the conclusion of the heavenly messages, this matter was tightly controlled, because it is from God the Almighty, the All-Knowing, the Wise, who does not favor anyone from his creation. Accurate and detailed in this case, and in all areas of life ... It has no parallel in the whole world .. And what happened to some minor breaches in some Islamic eras, as they do not represent Islam, and they have become a blasphemy against their perpetrators forever .... Imprisonment is one of the punishments that Islam has prescribed either to deter the perpetrator from the crime or to discipline him, or to restore people’s rights, but it is not a basic punishment, rather it is a discretionary punishment .... I have made this research in an introduction, an introduction, two articles and a conclusion. The first topic is the legality of imprisonment in Islamic jurisprudence and it is on two demands. Prisoners in Islamic jurisprudence, which is based on two demands. In the first request, I spoke about resources that achieve imprisonment, and I spoke in the second requirement about dealing with prisoners in Islamic jurisprudence, and I ask God to take in my hand what is good, righteous and good punishment.